Comprehensive Review on the Dynamic and Seismic Behavior of Flat-Bottom Cylindrical Silos Filled With Granular Material - Mansour, Sulyman; Pieraccini, Luca; Palermo, Michele; Foti, Dora; Gasparini, Giada; Trombetti, Tomaso; Silvestri, Stefano (Frontiers in Built Environment, 2022)
The seismic design of flat-bottom silos containing granular material still presents several challenges to be addressed. They are related to the main aspects which differentiate silo structures containing granular material from other civil structural typologies: (i) the relatively low self-weight of the silo structure as compared to the weight of the ensiled content; (ii) the granular nature of the ensiled material. Indeed, the internal actions in the structural members are governed by the complex dynamic interactions between the granular material and with the silo wall, the silo base or even the internal interaction between particles. More in detail, even though the scientific interest in such complex interactions dates back to the middle of the 19th century, several issues are still unclear such as the dependency of the fundamental dynamic properties (period of vibration and damping ratio) on the characteristics of the dynamic excitation (intensity, frequency content, duration) or the amount of ensiled material mass activated during a seismic excitation and provoking extra pressures on the wall (effective mass). Therefore, most of current seismic code provisions for silos are grounded on rather approximate and simplified assumptions leading to often over-conservative evaluations. The present paper intends to provide a comprehensive summary of the main acknowledged experimental, analytical and numerical advances in the dynamic and seismic behavior of silos, supporting the potential researcher in the field to understand the real differences between the standard recommendations and the actual conditions, as well as illustrating the open issues to be further investigated.